Investigating the Connection between Intercultural Communication Competence and Willingness to Communicate: A Case of Vietnamese EFL English Majors - Nguyen Thi, Xuan Hong (Technium Social Sciences Journal, 2026)
The global working environment demands understanding international affairs and the potential labour force; therefore, it necessitates possessing intercultural communication competencies. Built on the existing findings on this aspect worldwide, this study investigates whether EFL learners’ experiences in communicating with foreigners impact their intercultural communication competence (ICC) and willingness to communicate (WTC) among Vietnamese English students. The study was based on a survey of 109 participants at a university in HCM, Vietnam; the collected data were then analysed and interpreted. It has been found that there is an impact on students’ ICC experiences and their knowledge of WTC. These findings, to some extent, consolidate other research and clarify the need to facilitate EFL learners with expertise in intercultural communication.